Outdoor workers and sun protection strategies: Two case study examples in Queensland, Australia - Sendall, M.; Stoneham, Melissa; Crane, P.; Fleming, M.; Janda, M.; Tenkate, T.; Youl, P.; Kimlin, M. (Australian Rural Health Education Network, 2016)
Introduction: Outdoor workers are at risk of developing skin cancer because they are exposed to high levels of harmful ultraviolet radiation. The Outdoor Workers Sun Protection Project investigated sun protection strategies for high risk outdoor workers in rural and regional Australia. Methods: Fourteen workplaces (recruitment rate 37%) across four industries in rural and regional Queensland, Australia were recruited to the OWSPP. In 2011–2012, data were collected using pre- and post-intervention interviews and discussion groups. This article presents two workplaces as case study examples. Results: The flat organisational structure of workplace 1 supported the implementation of the Sun Safety Action Plan (SSAP), whilst the hierarchical organisational nature of workplace 2 delayed implementation of the SSAP. Neither workplace had an existing sun protection policy but both workplaces adopted one. An effect related to the researchers’ presence was seen in workplace 1 and to a lesser degree in workplace 2. Overt reciprocity was seen between management and workers in workplace 1 but this was not so evident in workplace 2. In both workplaces, the role of the workplace champion was pivotal to SSAP progression. Conclusions: These two case studies highlight a number of contextually bound workplace characteristics related to sun safety. These issues are (1) the structure of workplace, (2) policy, (3) an effect related to the researchers’ presence, (4) the workplace champion and (5) reciprocity. There are several recommendations from this article. Workplace health promotion strategies for sun safety need to be contextualised to individual workplaces to take advantage of the strengths of the workplace and to build capacity.